Solar powered traffic sensitive automated LED street lighting system - Ahmed, Sanjana; Tasneem, Nisat; Rahman, Md. Saidur; Zenan, Ahmed Hosne (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.